النظام المالي والضريبي في الجزائر في الفترة العثمانية من خلال الكتابة التاريخية المعاصرة " كتابات ناصر الدين سعيدوني نموذجا" - عباد هدى; بن نصيب أمال (My University, 2024)
summary The Ottoman period in the history of Algeria is considered one of the periods that still needs research and in-depth research in various fields, especially related to the economic aspect, which has witnessed great reluctance by many researchers and historians due to the scarcity of information related to this aspect, especially economic life, especially the financial and tax aspect, which It was considered the main pillar of the treasury revenues of the Algerian state at that time. However, despite this, some historians emerged, led by Professor Dr. Nasser al-Din Saidouni, who had great contributions to enriching the Algerian historical library, by contributing a group of works, most of which focused on studying the Algerian economy during The Ottoman era, and thus his writings became an important reference for writers and scholars interested in the economic history of Algeria in the Ottoman period. ---------------------------------- الملخص: تعتبر الفترة العثمانية من تاريخ الجزائر من ضمن الفترات التي لا تزال في حاجه الى البحث والتعمق وذلك في مختلف المجالات خاصة المتعلقة بالجانب الاقتصادي الذي عرف عزوفا كبيرا من طرف العديد من الباحثين والمؤرخين نظرا لشح المعلومات المتعلقة بهذا الجانب لا سيما الحياة الاقتصادية وخاصة الجانب المالي والضريبي الذي يعتبر الركيزة الأساسية لمداخيل الخزينة للإيالة الجزائرية آنذاك، الا انه رغم ذلك فقد برز بعض المؤرخين وعلى راسهم الاستاذ الدكتور ناصر الدين سعيدوني الذي كان له اسهامات جليلة في إثراء المكتبة التاريخية الجزائرية، من خلال المساهمة بمجموعة من المؤلفات والتي ركز في أغلبها على دراسة الاقتصاد الجزائري خلال الحقبة العثمانية، وبالتالي اصبحت كتاباته تعد مرجعا مهما للكتاب والدارسين المهتمين بتاريخ الجزائر الاقتصادي في الفترة العثمانية.
Keywords: : الضرائب، الدولة العثمانية، الجزائر، الرسوم، ناصر الدين سعيدوني